Simplicitas and the Hymni Ambrosiani - Tracy, Emmett Patrick (Trinity College (Dublin, Ireland). Department of Classics, 2013)
The overall aim of this thesis is to address the notion that the earliest and most influential of Christian poems, the Hymni Ambrosiani, were formally and linguistically simple. The general position that these highly structured verse compositions were the ‘simplest thoughts in the simplest forms of metre’ or functional and simple versiculi seems to overlook the complex and diverse literary and linguistic influences in the text. Despite the fact that the term simple remains an ambiguous and divisive concept in the modem age, little attention has been paid to its unsettling appropriation in Ambrosian poetic studies. Taking a formal and systematic approach, this work examines the syntax, lexis, and metre of the Hymni Ambrosiani and makes greater attempt to catalogue the poetic stylisations and the diverse linguistic influences in the collection.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin